Development of E-Learning Based Learning Media Assisted by Chamilo in Learning Physics to Improve Learning Outcomes of High School Students - Muniatuz Azairok; Apit Fathurohman (Postgraduate, University of Mataram, 2023)
The purpose of this research is to develop an E-learning-based learning media assisted by chamilo that can be used in teaching 12th grade high school students in odd semesters, especially in physics subjects, with the aim of delivering material and assignments in a structured manner. This research was conducted using the Research and Development (R&D) method and the Dick and Carey model. This journal discusses the results of the validation stage of the developed media. Data validation results were obtained from assessments by material physics experts, media experts, and learning experts. The validation results show positive results in these three aspects. The material aspect shows that the content presented is relevant and in accordance with the learning objectives. The media aspect shows the design and use of attractive and interactive media. Meanwhile, the learning aspect shows an efficient and interesting learning experience for students. The e-Learning product that has been developed can be a viable tool for educators in delivering material more efficiently and helping students achieve a better understanding in physics subjects. With good validation results, e-learning using Chamilo can be used as an effective and efficient learning medium to support the teaching and learning process, provide flexibility for students in accessing material, increase interaction with content, and increase efficiency in achieving learning goals.